2013
DOI: 10.1227/01.neu.0000429284.91142.56
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Economic Impact of Coiling vs Clipping for Unruptured Intracranial Aneurysms

Abstract: : SAH, subarachnoid hemorrhageUIAs, unruptured intracranial aneurysms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
33
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(36 citation statements)
references
References 36 publications
2
33
0
1
Order By: Relevance
“…First, administrative claims data including MarketScan and Medicare are routinely used for population-based comparative effectiveness research. 13 This data source reduces the common biases that result from selecting patients from particular surgeons, institutions, or regions, and reflects a nationally representative range of skill level and institutional size and volume. Although the data are not weighted to the national population, this reflects ETV outcomes in the real-world setting of up to one-sixth of the US population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, administrative claims data including MarketScan and Medicare are routinely used for population-based comparative effectiveness research. 13 This data source reduces the common biases that result from selecting patients from particular surgeons, institutions, or regions, and reflects a nationally representative range of skill level and institutional size and volume. Although the data are not weighted to the national population, this reflects ETV outcomes in the real-world setting of up to one-sixth of the US population.…”
Section: Discussionmentioning
confidence: 99%
“…While administrative claims data have been used to explore topics in adult neurosurgery, 13 it has not been used to investigate ETV in children. This study aims to use a large administrative database to describe the current practice, correlates, and effectiveness of ETV in pediatric patients in the US.…”
mentioning
confidence: 99%
“…9,10 The frequencies of aneurysm rests or recurrences are higher after coil embolization than that after surgical clipping. 11,12 Recent studies have revealed that recanalization after coil embolization occurs not only in the short term (typically within 1 year) but also in the long term (after several years). 1,[13][14][15][16] Repeated angiographic examinations or treatments because of the recanalization of coiled aneurysms result in a significant reduction in patient quality of life.…”
mentioning
confidence: 99%
“…They observed that although hospital length of stay and costs were higher in the clipping group for the initial procedure, whereas the overall costs at 2 and 5 years were similar in the clipping and coiling cohorts. [56] However, there is no true blinded randomized study that compares surgical clipping and Endovascular therapy.…”
Section: Surgical Clipping Versus Endovascular Therapy (Evt)mentioning
confidence: 99%